Pemanfaatan Teknologi Digital Dalam Strategi Marketing dan Pendampingan Pencatatan Laporan Keuangan Sederhana Pada UMKM Roti Bakar Manies - Salma Rahmi Ramadhani Putri; Yudas Tadius Andi Candra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This community service activity aims to help Roti Bakar Manies MSMEs increase their competitiveness through digital technology. The process begins with problem identification, followed by outreach about the importance of digital marketing and training on the use of social media and e-commerce platforms. Assistance to ensure the effectiveness of program implementation, then continues with the implementation stage and ends with evaluation to measure the success of the program. As a result, the digital marketing strategy succeeded in increasing the visibility and reach of the MSME market, thereby having a positive impact on sales. Apart from that, good financial management this also makes it easier to prepare more accurate financial reports. This program is expected to not only support the growth of MSMEs, but also contribute to the local economy and the welfare of the surrounding community.